Generalized Differential Quadrature Method for Free Vibration Analysis of a Rotating Composite Thin-Walled Shaft. (20th March 2019) - Zhong, Weiyan; Gao, Feng; Ren, Yongsheng
Abstract : A refined variational asymptotic method (VAM) and Hamilton's principle were used to establish the free vibration differential equations of a rotating composite thin-walled shaft with circumferential uniform stiffness (CUS) configuration. The generalized differential quadrature method (GDQM) was adopted to discretize and solve the governing equations. The accuracy and efficiency of the GDQM were validated in analyzing the frequency of a rotating composite shaft. Compared to the available results in literature, the computational results by the GDQM are accurate. In addition, effects of boundary conditions, rotating speed, ply angle, ratio of radius over thickness, and ratio of length over radius on the frequency characteristics were also investigated.